Interleukin-32γ in the Control of Acute Experimental Chagas Disease. (20th January 2022) - Braga, Yarlla L. L.; Neto, José R. C.; Costa, Arthur W. F.; Silva, Muriel V. T.; Silva, Marcos V.; Celes, Mara R. N.; Oliveira, Milton A. P.; Joosten, Leo A. B.; Ribeiro-Dias, Fátima; Gomes, Rodrigo S.; Machado, Juliana R.
Abstract : Chagas disease (CD) is an important parasitic disease caused by Trypanosoma cruzi . Interleukin-32 (IL-32) plays an important role in inflammation and in the development of Th1/Th17 acquired immune responses. We evaluated the influence of IL-32 γ on the immune response profile, pathogenesis of myocarditis in acute experimental CD, and control of the disease. For this, C57BL/6 wild-type (WT) and IL-32 γ Tg mice were infected subcutaneously with 1, 000 forms of Colombian strain of T. cruzi . In the histopathological analyzes, T. cruzi nests, myocarditis, and collagen were quantified in cardiac tissue. Cytokine productions (IL-32, IFN- γ, TNF- α, IL-10, and IL-17) were measured in cardiac homogenate by ELISA. The IL-32 γ Tg mice showed a better control of parasitemia and T. cruzi nests in the heart than WT mice. Infected-WT and -IL-32 γ Tg mice showed similar levels of IFN- γ, TNF- α, and IL-17, but IL-10 was significantly higher expressed in IL-32 γ Tg than in WT mice. The cytokine profile found in IL-32 γ Tg animals contributed to body weight maintenance, parasitemia control, and survival. Our results indicate that the presence of human IL-32 γ in mice infected with the Colombian strain of T. cruzi is important for infection control during the acute phase of Chagas disease.